2017
DOI: 10.1007/s00268-017-4161-x
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity Bypass Using Bovine Carotid Artery Graft (Artegraft): An Analysis of 124 Cases with Long‐Term Results

Abstract: BCAG is an excellent vascular conduit and provides good long-term results in lower extremity bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…The outcomes were promising, with patency up to 2 years even if applied in a low-flow district. A recent long-term study (2002–2017) showed the application of a bovine carotid artery graft (Artegraft) in lower extremity bypass surgery (Lindsey et al, 2017 ). Follow-up of 5 years of primary endpoints showed positive results for patency (66.7%) and salvage limb rates (81% of treated cases) (Table 1 ).…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…The outcomes were promising, with patency up to 2 years even if applied in a low-flow district. A recent long-term study (2002–2017) showed the application of a bovine carotid artery graft (Artegraft) in lower extremity bypass surgery (Lindsey et al, 2017 ). Follow-up of 5 years of primary endpoints showed positive results for patency (66.7%) and salvage limb rates (81% of treated cases) (Table 1 ).…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…When choosing a conduit for obturator bypass, even though studies have shown that while autologous vein may serve as the best graft, this is not an option in every patient. Lindsey et al found autologous vein was unsuitable for bypass in 72% of patients [5]. PTFE, however, is not the only alternative.…”
Section: Discussionmentioning
confidence: 99%
“…These poor outcomes were related to inappropriate processing, which resulted in insufficient mechanical properties to support the pressure of the circulatory system 217 and low antigen removal 218 . Having said that, recent reports on bovine artery crosslinked with starch dialdehyde (as opposed to GTA) have shown positive results as haemodialysis access 219 or as lower extremity bypass 220 . However, their implantation is not a generalized procedure, as their performance has not improved synthetic grafting.…”
Section: Xenografts In Clinical Indicationsmentioning
confidence: 99%